The Potential Malignancy of a Solitary Fibrous Tumour of the Lung - Rajeev Shukla; Davide Patrini; Elaine Borg; David Lawrence; Martin Hayward; Nikolaos Panagiotopoulos (Case Reports in Pathology)
Solitary fibrous tumours (SFTs) are rare neoplasms that in the majority of cases are benign. We present the case of a 52-year-old male, with a 23-year history of a slow growing pleural mass, presenting to our department with worsening dyspnoea and localised chest discomfort. The purpose of this case report is to highlight the potential malignancy of a solitary fibrous tumour of the lung along with the key features in diagnosis and management.